Teknologi Informasi Dan Komunikasi Dalam Pendidikan Di SD N 092/VII Pematang KOLIM I - Ahmad Ridwan; Evi Nurhidayati; Ermawati Ermawati; Kasmini Kasmini (Elkom: Jurnal Elektronika dan Komputer, 2024)
The role of information and communication technology in education in general aims to make students understand information and communication technology tools in general, including computers (literacy) and information literacy, where students recognize the terms used in information and communication technology. In the Qur'an there are so many commands, statements, suggestions and so on that substantially connect Islamic teachings with science and technology. The results of this research found that the role of information technology in education, apart from helping students in learning, also has a quite influential role for teachers, especially in the use of facilities to enrich teaching abilities, and the Al-Qur'an as a guide and guidance for the development of science and technology. in order to strengthen faith and improve human welfare.